Can open sourcing lead to inferior standards? - Kristian Koerselman (Aboa Centre for Economics (ACE), 2008)
I investigate the effect of open source on standardization outcomes in a market with positive network externalities. In a closed source world, it seems reasonable to assume that the probability of a standard being chosen is positively correlated with its quality. Open source may weaken or invert this relationship by giving Bertrand competition losers a second chance. It however follows that though open source leads to more competition and more standardization, the chosen standard will be the same as when open source is not an option.
Keywords: H41; L12; L86; L96; 330; open source software; FLOSS; standardization; network externalities; competition